Civics Education Learning Based on Local Cultural Values to Strengthen Students’ Civic Disposition - Novitasari Novitasari; Mashud Syahroni; Sukron Mazid; Firda Aulia Izzati; Arum Nisma Wulanjani (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
Students' civic disposition remains a challenge in Civics Education learning, particularly related to the implementation of contextual learning strategies which align with local culture. This study aimed to describe the process of integrating local cultural values into Civics Education subject and analyzed its impact on strengthening students' civic disposition. Using a mixed methods approach, quantitative methods were applied to measure the impact, while qualitative methods were used to explore the learning process. Value integration was carried out through individual portfolio assignments and group assignments analyzing character values in traditional games. The integrated character values included patriotism, law-abidingness, peace-loving, democratic, and creativity. The results showed that in the first class, there was an insignificant increase in civic disposition, while in the second class, there was a significant increase. These findings demonstrated that the integration of local cultural values can be effectively implemented in Civics Education learning, thus not only strengthening students' civic disposition but also fostering cultural awareness and strengthening national identity. This strategy has the potential to be an innovative alternative in developing Civics Education learning which is relevant to the Indonesian social and cultural context.